Prediksi Produksi Jagung dengan Menggunakan Metode Autoregressive Integrated Moving Average (ARIMA) - Julyanti , Nafi’ah Zahra; Azmi, Rinda Fitriana; Azizah, Istin Fitriani; Soraya, Siti (CORISINDO 2025, 2025)
West Nusa Tenggara (NTB) is one of the largest corn producing provinces in Indonesia, but its production has not been optimal to meet the increasing domestic and global demand. Along with the rapid growth of industry in the Asian region, the supply of corn in the world market tends to be limited, which is around 13% of the total world corn production, this creates a gap between demand and availability. This study aims to predict corn production trends in NTB using the Autoregressive Integrated Moving Average (ARIMA) method based on time series data from 2001–2023 from NTB Satu Data. The ARIMA method was chosen because of its ability to model historical data patterns without independent variables, making it suitable for short-term forecasting in the agricultural sector. The forecast results show that corn production in West Nusa Tenggara Province is expected to continue to increase from 2024 to 2028, with an average annual growth of 4.78%. However, this growth rate tends to decrease from year to year, indicating a slowdown in the rate of production growth. The use of the ARIMA method is effective as a prediction tool for strategic planning to increase corn production, reduce dependence on imports, and stabilize market prices.